2011
DOI: 10.3791/3069
|View full text |Cite
|
Sign up to set email alerts
|

Intraspinal Cell Transplantation for Targeting Cervical Ventral Horn in Amyotrophic Lateral Sclerosis and Traumatic Spinal Cord Injury

Abstract: Respiratory compromise due to phrenic motor neuron loss is a debilitating consequence of a large proportion of human traumatic spinal cord injury (SCI) cases 1 and is the ultimate cause of death in patients with the motor neuron disorder, amyotrophic laterals sclerosis (ALS) 2 .ALS is a devastating neurological disorder that is characterized by relatively rapid degeneration of upper and lower motor neurons. Patients ultimately succumb to the disease on average 2-5 years following diagnosis because of respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Several contusion models at mid-cervical levels (C3, C4, C5) that show chronic abnormalities in respiratory parameters have been developed in the rat. [22][23][24][25] The extension of a contusion injury model to the mouse provides opportunities for manipulating genes of interest and for evaluating their role in relevant outcome measures affected by cervical spinal contusion such as forelimb motor function, respiratory function, and neuropathic pain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several contusion models at mid-cervical levels (C3, C4, C5) that show chronic abnormalities in respiratory parameters have been developed in the rat. [22][23][24][25] The extension of a contusion injury model to the mouse provides opportunities for manipulating genes of interest and for evaluating their role in relevant outcome measures affected by cervical spinal contusion such as forelimb motor function, respiratory function, and neuropathic pain.…”
Section: Resultsmentioning
confidence: 99%
“…The dorsal skin and underlying muscle layers were incised along the midline between the spinous processes of C2 and T1 to expose the cervical region of the spinal cord. 24 The dorsal muscle layers were retracted, and the paravertebral muscles overlying C4-C6 were removed. Following unilateral laminectomy on the right side at C4 and C5 levels, mice were subjected to a double spinal contusion injury at both C4 and C5 levels using the Infinite Horizon (IH) impactor (Precision C5 double contusion 3 3 6 3 6 9…”
Section: Unilateral Cervical Spinal Cord Contusionmentioning
confidence: 99%
“…Several studies have demonstrated that the transplantation of UC-MSCs is a potential therapeutic strategy for the treatment of central nervous system diseases, including cerebrovascular disease, nerve degenerative diseases, spinal cord injury and cerebral palsy. The transplantation path in cell therapy is diverse (14)(15)(16) and mainly includes the intervention path, local implantation, intravenous route and lumbar puncture way. Migration toward pathology is the first critical step in UC-MSCs engagement during regeneration and it is hypothesized that the…”
Section: Discussionmentioning
confidence: 99%
“…The dorsal skin and underlying muscle layers were incised along the midline between the spinous processes of C2 and T1 [25–27]. Following right unilateral laminectomy, mice were administered 100,000 GRP in 2 ÎĽl in the ventral horns of both C4 and C5 levels, at a depth of 0.75 mm.…”
Section: Methodsmentioning
confidence: 99%